Current and future socio-ecological vulnerability and adaptation of artisanal fisheries communities in Peru, the case of the Huaura province. (September 2020) - Jara, Hans J.; Tam, Jorge; Reguero, Borja G.; Ganoza, Francisco; Castillo, Gladis; Romero, Carlos Y.; Gévaudan, Manon; Sánchez, Américo A.
Abstract: Marine artisanal fisheries make vital contributions to food security, livelihoods, jobs, and income in coastal communities globally. However, resources vary as a result of changes in oceanographic conditions such as sea surface temperature or wind stress, which impacts communities and also makes them more sensitive to other stressors such as climate change. In Peru, small-scale fisheries are paramount to the country's economy and food security. They are also one of most globally affected by interannual changes and potentially impacted by climate change. Assessing their present and future vulnerability and finding adaptation strategies are key to the sustainability of the sector and the livelihoods of many. This study assesses the local vulnerability in the Huaura province, Peru, where three fishing communities of very different socio-economic characteristics share the same fishing ground. The region is very sensitive to changes associated with El Niño. We assess the ecological and socio-economic vulnerability using governmental and local information, to pinpoint the main drivers of vulnerability. We find stark differences between communities: Carquín shows the greatest dependence on artisanal fishing for income and a low adaptive capacity, whereas Huacho, a larger and more diversified economy, presents greater livelihood alternatives for the artisanal fishermen. The future vulnerability analysis highlights the need to implement adaptation measures, including: economic diversification; forms to add value to the artisanal fishing; sustainable management of fishing grounds; and actions that help manage shocks from interannual variations, such as monitoring and prediction systems, but also financing mechanisms that could attenuate the socio-economic impacts.